Analysis of thermal comfort experience using peak-end rule with air conditioner in heating season. (1st February 2023) - Yang, Zixu; Cui, Mengdi; Xiao, Hansong; Sun, Hongli; Wang, Baolong; Lin, Borong; Shi, Wenxing
Abstract: Recent years have seen a significant increase in study on the thermal comfort offered by room air conditioners (RACs) when utilized as heaters, especially in the steady stage. Research indicates that convective terminals can form a comfortable environment using optimized control settings and strategies. Nevertheless, complaints about the thermal comfort experienced when using RACs persist, which is probably related to cognitive bias in psychology. The final seconds of an experience are given a lot of weight by the peak-end rule, which is typically characterized as the positive/negative peak. They were used to analyze how different heating experiences rated in terms of thermal comfort. Therefore, dynamic indoor temperature variations with six different terminals and control strategies were analyzed. Furthermore, an experiment with a thermal sensation, thermal comfort, thermal preference, and thermal adaptability vote (TSV, TCV, TPV and TAV) with different dynamic controlling characteristics was conducted in an artificial chamber. Three control methods with different peak moments were determined: slow start, interval downtime operation, and continuous heating. The comprehensive experience TCVs were 2.72, 2.28, and 1.12, and average-weighted TCVs were 1.94, 1.60, and 1.14, respectively. This exhibited a significant difference in terms of the heating process evaluation. In contrast, the TCVs based on the peak-end rule were 2.52, 2.31, and 1.11, respectively, which is more consistent with field evaluation. There is strong evidence that peak-end rule applies to TCV for air-conditioning systems. Other cognitive biases were also analyzed to evaluate the heating experience. Reasons for the thermal discomfort of RACs are also summarized. Graphical abstract: Image 1 Highlights: Cognitive bias existed in the comprehensive evaluation of the heating experience. Peak-end rule was used to analyze experience thermal comfort of air conditioner. Reasons for the thermal discomfort of RACs are summarized.